Free Radical Scavenging Activity of Leucas indica Flowers and Leaves - Vinayagam, A.; Sudha, P.N. (Asian Journal of Chemistry, 2013)
Present work was undertaken to study antioxidant free radical scavenging activity of leaves and flowers extracts of Leucas indica. Crude methanolic extracts was screened for in vitro antioxidant free radical scavenging activity by diphenyl picryl hydrazyl, nitric oxide radical scavenging and superoxide radical scavenging assay methods. Results showed that IC50 value of methanol extracts of leaves in diphenyl picryl hydrazyl, nitric oxide scavenging and superoxide radical scavenging assays are 241.11, 282.97 and 250.45 μg/mL. Similarly IC50 value of methanol extracts of flowers in diphenyl picryl hydrazyl, nitric oxide scavenging and superoxide radical scavenging assays are 0.19, 2.05 and 2.15 μg/mL, respectively. Phytochemical screening revealed that flavonoids, alkaloids and phenolic compound are present in methanol extracts of leaves and flowers and may be responsible for the antioxidant activity. The result showed that Leucas indica flowers are more potential free radical scavenging activity than leaves.